2018
DOI: 10.3389/fimmu.2018.02961
|View full text |Cite
|
Sign up to set email alerts
|

To B or Not to B: Understanding B Cell Responses in the Development of Malaria Infection

Abstract: Malaria is a widespread disease caused mainly by the Plasmodium falciparum (Pf) and Plasmodium vivax (Pv) protozoan parasites. Depending on the parasite responsible for the infection, high morbidity and mortality can be triggered. To escape the host immune responses, Plasmodium parasites disturb the functionality of B cell subsets among other cell types. However, some antibodies elicited during a malaria infection have the potential to block pathogen invasion and dissemination into the host. Thus, the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 88 publications
(101 reference statements)
1
41
0
1
Order By: Relevance
“…This has been proposed as a mechanism to avoid the establishment of efficient and long‐lasting humoral responses . Notably, the development of naturally acquired immunity against Plasmodium is very slow and might take several years and is associated with a very low frequency of Plasmodium ‐specific memory B cells detected in populations from malaria endemic areas . Studies using murine and non‐human primate models have suggested impaired induction and maturation of germinal centers (GCs) thus leading to the production of low‐affinity, short‐lived antibody responses and the development of limited B cell memory.…”
Section: Co‐infection With Plasmodium Parasites Modulates Chikv Pathomentioning
confidence: 99%
See 2 more Smart Citations
“…This has been proposed as a mechanism to avoid the establishment of efficient and long‐lasting humoral responses . Notably, the development of naturally acquired immunity against Plasmodium is very slow and might take several years and is associated with a very low frequency of Plasmodium ‐specific memory B cells detected in populations from malaria endemic areas . Studies using murine and non‐human primate models have suggested impaired induction and maturation of germinal centers (GCs) thus leading to the production of low‐affinity, short‐lived antibody responses and the development of limited B cell memory.…”
Section: Co‐infection With Plasmodium Parasites Modulates Chikv Pathomentioning
confidence: 99%
“…This was supported by previous findings where apoptosis in lymph nodes and secondary lymphoid organs upon malaria infection was described. 133,134 In addition, it is also known that blood-stage malaria infections suppress dendritic cell (DC) responses by affecting DC maturation, [142][143][144] reducing surface expression of MHC-II 142,[145][146][147] and co-stimulatory molecule CD86, 146 inducing DC apoptosis 148,149 and impairing their ability to process and present parasite-derived antigens to T cells. 150,151 In line with this, reduced numbers of conventional DCs in the pLN of co-infected mice were also observed, suggesting that reduced expansion of CD4 + T cells might be due in part to the drop in DCs numbers associated with malaria.…”
Section: Immune Modulation Of Chikv T Cell Responses By Plasmodium mentioning
confidence: 99%
See 1 more Smart Citation
“…Although performance data for several of these assays have been rapidly communicated by different laboratories (4)(5)(6)(7)(8), to our knowledge no reports are available yet on the applicability of these tests on African serum panels. Here, assay specificity may be challenged by previous or current infections with other pathogens; in particular, hypergammaglobulinemia induced by Plasmodium infection may cause false positive results in serological tests (9,10).…”
mentioning
confidence: 99%
“…A transcrição de um lncRNA (bloco laranja) pode afetar positivamente (1) ou negativamente (2 e 3) a expressão de um gene codificador de proteína (blocos azuis) através da indução de remodelamento da cromatina ou da inibição do recrutamento da RNA polimerase II e silenciamento epigenético, respectivamente. A hibridização de um lncRNA antisenso (bloco rosa) com um mRNA senso (blocos azuis) pode levar à degradação do mRNA (4) ou ao bloqueio do reconhecimento de um exon (bloco roxo) pelo spliceossomo causando uma alteração no padrão de splicing do mRNA (5). LncRNAs (bloco preto) também podem ser processados em RNAs pequenos como microRNAs, piRNAs, dentre outros (6).…”
Section: Figura 4 Algumas Funções Atribuídas Aos Longos Rnas Não-codunclassified